2014
DOI: 10.1111/imj.12351
|View full text |Cite
|
Sign up to set email alerts
|

Examining patients' preferences for participation in clinical decision‐making: the experience in a Latin American chronic obstructive pulmonary disease and cancer outpatient population

Abstract: While they considered the role of their families relevant and wanted information to be shared so that family members might participate in decision-making, they did not want their families to have a right to withhold information, make final decisions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 41 publications
0
1
0
1
Order By: Relevance
“…Furthermore, patients expect their HCPs to explain treatment benefits and risks specific to their individual scenario [21]. Those who are more likely to desire SDM include: younger patients [5,19,22], females [5,20,22], and/or those with a severe diagnosis [5,23]. In contrast to patient desires/preferences, previous studies have found only 39% of patients felt that SDM occurred in their consultations [21], and 37% were involved less than they wished to be [24].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, patients expect their HCPs to explain treatment benefits and risks specific to their individual scenario [21]. Those who are more likely to desire SDM include: younger patients [5,19,22], females [5,20,22], and/or those with a severe diagnosis [5,23]. In contrast to patient desires/preferences, previous studies have found only 39% of patients felt that SDM occurred in their consultations [21], and 37% were involved less than they wished to be [24].…”
Section: Introductionmentioning
confidence: 99%
“…As boas notícias contribuem para o bem-estar dos familiares e mulheres que esperam bons resultados e as notícias ruins podem desestruturar, exigindo uma adaptação para o momento. Uma pesquisa latino-americana indicou que a maioria dos pacientes com câncer pulmonar não desejava ser impedida de conhecer a verdade por suas famílias e queria participar de todo o processo de decisão do tratamento (Jordan, Quadrelli, Heres, 2014). Os pacientes esperam e aguardam a comunicação do curso da doença e do seu tratamento.…”
Section: De Acordo Comunclassified